ELECTROMAGNETIC ELECTRON-CYCLOTRON WAVES WITH AC FIELD IN THE MAGNETOSPHERE - Kaur, Rajbir; Pandey, R.S.; Kumar, S.; Tomar, B.S. (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In this paper the effect of externally injected beam of cold electrons on electromagnetic electron-cyclotron (EMEC) waves in the magnetosphere has been discussed. The investigation is conducted using the methodology of characteristic solution and considering kappa distribution function in the presence of AC field. The objective of present study is to examine the variation in growth rate of EMEC waves when temperature anisotropy, magnitude of AC field and number density of energetic particles varies. It is inferred that EMEC waves grow more significantly when propagating oblique to magnetic field direction rather than parallel to magnetic field direction. Also that as the temperature anisotropy and number density of background plasma increases, growth rate of EMEC waves increases.